1 & 2 Timothy and Titus - Long, Thomas G. (Belief: a theological commentary on the Bible, 2016)
"Thomas G. Long's insightful commentary on the Pastoral Epistles argues that these often-neglected letters are urgently important for readers today. Some of the issues faced by New Testament churches are ours as well: the lure and peril of "spirituality" for Christians, the character of authentic worship, the qualities needed for sound leadership, and the relationship between family life and the church. Long's interpretations of these books consider contemporary exegetical and theological outlooks and are presented through his seasoned homiletical and pastoral perspectives. Pastors will be strengthened by Long's view that the Pastoral Epistles can refresh our memory about what really counts in the Christian community and how important trustworthy leaders are"--